2016
DOI: 10.5507/fot.2016.014
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted characterization of a Lemanea fluviatilis population (Batrachospermales, Rhodophyta) from a glacial stream in the south-eastern Alps

Abstract: Abstract:The aim of this study was a combined and multifaceted characterization (morphological, molecular, lipid, pigment, and ecological data) of a Lemanea (freshwater red alga) population from the south-eastern Alps, exploring its adaptive strategies to the montane habitat, (turbulent, very-cold glacial stream with extremely low-conductivity). Although the thalli were small (only up to 1 cm), the morphology was within the current circumscription of Lemanea fluviatilis. The molecular data placed this populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…paradoxa does not present peculiar features. It meets expectations for an alga belonging to the Ulvophyceae, with lutein, neoxanthin, violaxanthin, and α/β-carotene as the most abundant carotenoids, besides, among essential photosynthetic pigments, chlorophyll a and chlorophyll-b Some environmental characteristics, such as temperature and nutrient (specifically P) availability, are important abiotic drivers affecting lipid-class composition of algal cell membranes, and thus their fluidity and permeability, and P content (Saber et al 2016;Gonzalez-Silvera et al 2017;Hayashida et al 2017). In this study, the inter-classes distribution of the membrane lipids was in line with our expectations revealing the presence of several lipid species in all the relevant classes MGDG, DGDG, SQDG, and DGTS.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…paradoxa does not present peculiar features. It meets expectations for an alga belonging to the Ulvophyceae, with lutein, neoxanthin, violaxanthin, and α/β-carotene as the most abundant carotenoids, besides, among essential photosynthetic pigments, chlorophyll a and chlorophyll-b Some environmental characteristics, such as temperature and nutrient (specifically P) availability, are important abiotic drivers affecting lipid-class composition of algal cell membranes, and thus their fluidity and permeability, and P content (Saber et al 2016;Gonzalez-Silvera et al 2017;Hayashida et al 2017). In this study, the inter-classes distribution of the membrane lipids was in line with our expectations revealing the presence of several lipid species in all the relevant classes MGDG, DGDG, SQDG, and DGTS.…”
Section: Discussionsupporting
confidence: 61%
“…The lower UI values of the plastidial DGDG and SQDG lipids appear to play a pivotal role in maintaining adequate membrane fluidity in this thermal habitat. In accordance with this observation, Saber et al (2016) inversely documented a high unsaturation index (UI) and long acyl chains for the plastidial lipid class monogalactosyl diacylglycerols (MGDG) of the red alga Lemanea fluviatilis inhabiting a cold, glacial alpine habitat, as an adaptive strategy for maintaining adequate membrane fluidity and all metabolic processes. In addition, the presence of more saturated acyl chains in the DGDG and SQDG lipid classes could be another physiological adaptation of U. flexuosa subsp.…”
Section: Discussionmentioning
confidence: 56%
“…between grazing invertebrates and primary producers in alpine streams (e.g., Cummins and Klug 1979, Mihuc and Toetz 1996, Zah et al 2001, Füreder et al 2003, Niedrist and Füreder 2018, studies of potential bottomup effects or quantifications of the relationship between compartments are scarce in such environments (Taylor et al 2002). Many epilithic diatoms, several cyanobacteria, some green algae, and a few golden-brown (chrysophytes) and red algae (e.g., Saber et al 2016) colonize benthic habitats in alpine (above the treeline) and subalpine streams (e.g., Hieber et al 2001, Rott et al 2006, and community composition and biomass vary between stream types (Rott et al 2006) and seasons (Rott et al 2000, Hieber et al 2001.…”
mentioning
confidence: 99%
“…Two datasets were used for the phylogenetic analyses: the rbcL dataset included 42 taxa and 1 Tuomeya as an outgroup, and the SSU dataset included 13 taxa and 2 Balbiania taxa as outgroups. The outgroup taxa were selected according to previous studies [10,12]. The pairwise genetic distances between each specimen were computed in MEGA 5.0 [36].…”
Section: Morphological Characterizationmentioning
confidence: 99%
“…In recent years, it was found that species identified by morphology were not in the same clade identified using molecular evidence [9]. The morphology of Lemanea varies with the season and water conditions including salinity, temperature and flow velocity [10,11]. The systematics and diversity of Lemanea based only on traditional morphology were not reliable and thus needed revision using molecular methods.…”
Section: Introductionmentioning
confidence: 99%